Indicators of the Immune Status in Children after a New Coronavirus Infection - E. V. Moskaleva (Scientific Сentre for Family Health and Human Reproduction Problems, 2021)
Background. The mechanism of the immune response in patients with COVID-19 is still poorly understood and differs from other respiratory infections. Immunodeficiencies and age-related characteristics of immunity can be regarded as factors influencing reinfection and a predisposition to prolonged persistence of SARS-CoV-2. Most of the studies report about post-infection immunity to SARS-CoV-2 for adults and less for children. However, understanding the dynamics of antibody production to SARS-CoV-2 among children as well as other unique features of immune response is extremely important, because this provides to avoid possible complications and long-term outcomes of COVID-19, and predict the epidemic spread of the new coronavirus in the organized groups of children such as kindergartens, schools, study groups and clubs.Aim: to evaluate the humoral and cellular immunity after SARS-CoV-2 infection in children.Materials and methods. We reported data of the first phase prospective cohort study of immunity among 60 children living in Irkutsk, Russia within a month after SARS-CoV-2 infection, which took place in October and November 2020.Results. Immunity of children one month after SARS-Cov-2 infection was characterized by suppressed cell-mediated and humoral immunity, and phagocytosis dysfunction. Reduced phagocytosis by neutrophils was noted for 61.6 % of individuals.Conclusions. Children after COVID-19 had impaired immunity to SARS-CoV-2, which may be a predictor of chronic infection and other long-term outcomes of COVID-19.